Pemberdayaan Berbasis Masyarakat melalui Produksi Makanan Berbahan Baku Ikan - Yanti Mutalib; Siswadi Sululing; Maulana Wahyu Ayatullah; Arianti A. Ogotan; Frederik Dony Sangkia (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity (CSP) is entitled: Community-Based Empowerment Through Fish-Based Food Production. The target of this activity is the wives of fishermen from the Poklashar Kadompe group in Tinangkung Village, Tinangkung Selatan District, BangKep Regency. The problems faced by the partner group are (1) fish are only sold raw at very cheap prices so the profits are small, (2) lack of knowledge and skills in processing fish-based food, (3) lack of equipment due to limited business capital, (4) lack of insight and skills in making attractive product packaging, (5) knowledge about product marketing which is still minimal, (6) lack of understanding about business management. The purpose of this CSP is to empower fishermen's wives to become entrepreneurs of processed products, meatballs and fish floss. The implementation method is the Pelatihan and counseling method starting from: product production and packaging techniques, promotion techniques, marketing and business management as well as group financial bookkeeping. The outputs of CSP are fish meatball and fish floss products, activity videos https://youtu.be/WtyWCBukn6c?si=1Dpr8_DJcK3FfrHG and publications in online mass media https://www.sangalu.com/daerah/8313512169/didanai-hibah-drtpm-tahun-2024-tim-pkm-unismuh-uwuk-banggai-gelar-pelatihan-produksi-makanan-berbahan-baku-ikan-di-desa-tinangkung and publication of articles in the PakMas journal (Sinta 4) journal link https://journal.yp3a.org/index.php/pakmas/about and community service posters.